(5a+3b)^2 - (5a-3b)^2

asked by guest
on Mar 20, 2025 at 8:54 pm



You asked:

Evaluate the expression: (5a+3b)2(5a3b)2{\left( 5 a + 3 b \right)}^{2} - {\left( 5 a - 3 b \right)}^{2}

MathBot Answer:

Evaluated



(5a+3b)2(5a3b)2=(5a3b)2+(5a+3b)2\displaystyle {\left( 5 a + 3 b \right)}^{2} - {\left( 5 a - 3 b \right)}^{2} = - \left(5 a - 3 b\right)^{2} + \left(5 a + 3 b\right)^{2}


Expanded

(5a+3b)2(5a3b)2=60ab{\left( 5 a + 3 b \right)}^{2} - {\left( 5 a - 3 b \right)}^{2} = 60 a b


Factored

(5a+3b)2(5a3b)2=60ab{\left( 5 a + 3 b \right)}^{2} - {\left( 5 a - 3 b \right)}^{2} = 60 a b